Simbol-simbol Promosi Pariwisata dalam Film Romantis Remaja 'Dilan 1990' untuk Kota Bandung - Ida Ayu Etsa Pracintya; I Nyoman Darma Putra; Putu Sucita Yanthy (Institut Seni Indonesia Denpasar, 2022)
Film induced tourism is one of the fastest growing sectors in the tourism industry because cinematographic history is able to persuade the audience to travel to places that are used as the setting places of several scenes in a film. This study aims to examine the message of tourism promotion in a teenager romantic film set in Bandung, West Java, entitled ‘Dilan 1990’ which was adapted from a novel by Pidi Baiq of the same title. The data were collected by observing the film using observation tables, as well as audience reviews obtained through internet searches as a reference in interpreting symbols and knowing the audience's reception of this film. The audience’s reviews were taken from various websites including the Internet Movie Database, TripAdvisor, and from several independent travel blogs articles. The analysis used a qualitative descriptive method using three theories, namely, the theory of semiotics, reception, and promotion. The analysis shows that symbols of tourism promotion in the content of the film ‘Dilan 1990’ included the beautiful and clean city of Bandung, Bandung’s natural scenery, and Bandung’s heritage iconic buildings. The positive images of Bandung city were aesthetically presented on the film through well-structured of plot story, scene, and acting, thus make the promotion of Bandung become indirectly powerful. This study also stresses that the ‘Dilan 1990’ not only provide a powerful form of promotion for Bandung city but also has inspired the local government to build new city parks namely ‘Taman Dilan 1’ and ‘Taman Dilan 2’ that boosted the images of Bandung as an attractive city to visit.